1996
DOI: 10.1523/jneurosci.16-15-04638.1996
|View full text |Cite
|
Sign up to set email alerts
|

APPL, theDrosophilaMember of the APP-Family, Exhibits Differential Trafficking and Processing in CNS Neurons

Abstract: The Drosophila Appl gene encodes a transmembrane protein that is expressed exclusively in neurons. Amino acid comparisons show that APPL protein is a member of the amyloid precursor protein (APP)-like family of proteins. Similar to mammalian APP-family proteins, APPL is synthesized as a transmembrane holoprotein and cleaved to release a large secreted amino-terminal domain. Using immunocytochemical methods, we have analyzed the distribution of APPL in the Drosophila CNS. Surprisingly, although APPL is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 62 publications
7
54
0
Order By: Relevance
“…were mouse anti-Armadillo (N27A1, 1:50, Iowa Hybridoma Bank), rat anti-elav (7E8A10, 1:500, Iowa Hybridoma Bank), rabbit anti-b-gal (1:1000, Sigma), mouse anti-GFP (1:200, Sigma), rat anti-Ci (2A1, 1:3), 38 rabbit anti-Cul1 (1:250, Zymed), rabbit anti-cleaved (activated) caspase 3 (1:50, Cell Signaling Technology), rabbit anti-phospho-histone H3 (1:500, Upstate Biotechnology), rabbit anti-APPL (Ab952, 1:500), 21 and mouse anti-Myc (1:200, Roche). Secondary antibodies coupled to the appropriate fluorophore (FITC, Cy3, or Cy5; Jackson Immunoresearch Laboratories) were diluted to 1:200 in wash solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…were mouse anti-Armadillo (N27A1, 1:50, Iowa Hybridoma Bank), rat anti-elav (7E8A10, 1:500, Iowa Hybridoma Bank), rabbit anti-b-gal (1:1000, Sigma), mouse anti-GFP (1:200, Sigma), rat anti-Ci (2A1, 1:3), 38 rabbit anti-Cul1 (1:250, Zymed), rabbit anti-cleaved (activated) caspase 3 (1:50, Cell Signaling Technology), rabbit anti-phospho-histone H3 (1:500, Upstate Biotechnology), rabbit anti-APPL (Ab952, 1:500), 21 and mouse anti-Myc (1:200, Roche). Secondary antibodies coupled to the appropriate fluorophore (FITC, Cy3, or Cy5; Jackson Immunoresearch Laboratories) were diluted to 1:200 in wash solution.…”
Section: Methodsmentioning
confidence: 99%
“…20 Different forms of Drosophila APPL protein are enriched in different areas of the brain. 21 Deletion of the Appl gene does not cause obvious defects in adult brain morphology. 20 However, loss-and gain-of-function studies have revealed a role for APPL in synapse differentiation and axonal transport.…”
mentioning
confidence: 98%
“…APP is expressed at relatively high levels in the central nervous system of diverse species (6,7). Multiple APP isoforms are derived from a single gene by alternative splicing (see Ref.…”
mentioning
confidence: 99%
“…This indicates functional conservatism between Drosophila Appl and human АРР [Luo et al, 1992]. Many researches specify the key role of Appl in formation and maintenance of synapses in Drosophila [Ashley et al, 2005;Torroja et al, 1996]. Experiments by definition of Appl localization have shown significant Appl enrichment in growing axons and synaptic www.intechopen.com structures and participation of Appl in formation and differentiations of synapses in neuromuscular junctions of larvae [Torroja et al, 1996[Torroja et al, , 1999b.…”
Section: Drosophila Models Of Alzheimer's Amyloidosismentioning
confidence: 99%
“…Many researches specify the key role of Appl in formation and maintenance of synapses in Drosophila [Ashley et al, 2005;Torroja et al, 1996]. Experiments by definition of Appl localization have shown significant Appl enrichment in growing axons and synaptic www.intechopen.com structures and participation of Appl in formation and differentiations of synapses in neuromuscular junctions of larvae [Torroja et al, 1996[Torroja et al, , 1999b. The overexpression both Appl, and human АРР caused disturbance of axon transport [Gunawardena and Goldstein, 2001;Torroja et al, 1999a].…”
Section: Drosophila Models Of Alzheimer's Amyloidosismentioning
confidence: 99%